A step into the unknown: universities and the governance of regional economic development. Issue 7 (2nd July 2016) - Pugh, Rhiannon; Hamilton, Eleanor; Jack, Sarah; Gibbons, Amy
ABSTRACT: As the social and economic landscape changes, universities are coming under growing pressure to contribute to the economic development of their localities. This paper explores the increasing trends towards universities as key actors in the governance of regional economic development through activities to support economic and entrepreneurship development in their regions. A case study is presented of an institution in the UK which is increasingly situating itself in the economic governance sphere. Drawing on the experiences of those working at the coalface of economic governance activities, the opportunities and potential challenges faced by a university when engaging in such activities are explored. The ultimate goal of this paper is to shed light on universities' activities in the realm of regional economic governance, an area currently under-explored in extant literature.